MAP7 and MUCL1 Are Biomarkers of Vitamin D3-Induced Tolerogenic Dendritic Cells in Multiple Sclerosis Patients - Navarro-Barriuso, Juan; Mansilla, María José; Quirant-Sánchez, Bibiana; Ardiaca-Martínez, Alicia; Teniente-Serra, Aina; Presas-Rodríguez, Silvia; ten Brinke, Anja; Ramo-Tello, Cristina; Martínez-Cáceres, Eva M. (Frontiers in Immunology, 2019)
The administration of autologous tolerogenic dendritic cells (tolDC) has become a promising alternative for the treatment of autoimmune diseases, such as multiple sclerosis (MS). Specifically, the use of vitamin D3 for the generation of tolDC (vitD3-tolDC) constitutes one of the most widely studied approaches, as it has evidenced significant immune regulatory properties, both in vitro and in vivo. In this article, we generated human vitD3-tolDC from monocytes from healthy donors and MS patients, characterized in both cases by a semi-mature phenotype, secretion of IL-10 and inhibition of allogeneic lymphocyte proliferation. Additionally, we studied their transcriptomic profile and selected a number of differentially expressed genes compared to control mature and immature dendritic cells for their analysis. Among them, qPCR results validated CYP24A1, MAP7 and MUCL1 genes as biomarkers of vitD3-tolDC in both healthy donors and MS patients. Furthermore, we constructed a network of protein interactions based on the literature, which manifested that MAP7 and MUCL1 genes are both closely connected between them and involved in immune-related functions. In conclusion, this study evidences that MAP7 and MUCL1 constitute robust and potentially functional biomarkers of the generation of vitD3-tolDC, opening the window for their use as quality controls in clinical trials for MS.